"Why Should Our Bodies End at the Skin?": Embodiment, Boundaries, and Somatechnics - SHILDRICK, MARGRIT (Hypatia, 2015)
Donna Haraway's enduring question—"Why should our bodies end at the skin?" (Haraway 1990, 220)—is ever more relevant in the postmodern era, where issues of bodies, boundaries, and technologies increasingly challenge not only the normative performance of the human subject, but also the very understanding of what counts as human. Critical Disability Studies has taken up the problematic of technology, particularly in relation to the deployment of prostheses by people with disabilities. Yet rehabilitation to normative practice or appearance is no longer the point; instead, the lived experience of disability generates its own specific possibilities that both limit and extend the performativity of the embodied self. I look at what is at stake in the challenge to the Western logos that comes specifically from the capacities of the disabled body, understood not as a less than perfect form of the normative, but as figuring difference in a nonbinary sense. Feminist theory has long contested the isomorphism of the logos, but I go beyond simply setting out the grounds for revaluing multiple variant forms. The feminist turn to Jacques Derrida and Gilles Deleuze opens up the problematic to a celebratory positioning of difference and transcorporeality as the very conditions of life.
Keywords: EDI; approches et analyses; arts; bioéthique; corps; cours; discipline; philosophie; postmodernisme; premier cycle; prothèses; ressource en ligne; sciences; sciences humaines; sex1911; sex1920; technologie; thématiques; études critiques du handicap; études littéraires

Thinking fragments: Psychoanalysis, feminism, and postmodernism in the contemporary west - Flax, Jane (University of California Press, 1990)
Thinking Fragments provides a brilliant critique of psychoanalytic, feminist, and postmodern theory. Examining the writings of Freud, Winnicott, Lacan, Chodorow, Irigaray, Derrida, Rorty, and Foucault, among others, Flax conducts a "conversation" among psychoanalysts, feminist thinkers, and postmodern theorists, evaluating the ways in which each group of thinkers succeeds in coming to terms with crises in contemporary Western culture. As she analyzes each theory in turn, the others are used to identify and interrogate its gaps and omissions. The result is a postmodern text of intertwined ideas, devoid of clear beginnings, endings, conclusions. Flax addresses the question, "how is it possible to theorize in the contemporary West?" With the demise of objective notions of truth, knowledge, self and power, intellectuals have devised these new modes of thinking which both reflect and contribute to the uncertainties of the contemporary West. Each also addresses at least one aspect of what has become most problematic to modern individuals: How to come to terms with self, gender, knowledge and power without resorting to concepts that stress objectivity, universal knowledge, and a unitary self. Flax finds that neither psychoanalysis, nor feminism, nor postmodernism is adequate to the task for which it was conceived. Each can illuminate certain aspects of problems of self, gender, knowledge, and power, but none is sufficient on its own. In fact, each incorporates characteristic blindnesses rooted in part in the very difficulties it addresses. Despite their failures, Flax concludes that these modes of theorizing are our best tools thus far, compelling us to use them even while we grapple with the problems they raise. Thinking Fragments is a wide-ranging study that will elicit much discussion and debate. It is an essential text for social scientists and humanists alike, as well as anyone else who thinks about how to "do" theory in the contemporary West.
Keywords: 1900-1999; approches et analyses; cours; discipline; fem1000; occident; postmodernisme; premier cycle; psychanalyse; périodes historiques; ressource en ligne; sciences; sciences humaines